Liquid phase exfoliation of graphene using ammonia as an easy-to-remove additive in low-boiling organic-water co-solvent suspensions - Martin Nastran; Paul Peschek; Izabela Walendzik; Jakob Rath; Bernhard Fickl; Jasmin S. Schubert; Wolfgang Ipsmiller; Andreas Bartl; Gerd Mauschitz; Gabriel Szabo; Richard A. Wilhelm; Jochen Schmidt; et al. (Communications Chemistry)
Abstract Graphene nanosheets from suspensions are key to applications such as in printable films, battery/supercapacitor electrodes, fillers in composite materials or catalyst supports. We present a straightforward method for achieving high-concentration and long-term stable graphene suspensions by liquid phase exfoliation (LPE) via a combination of ammonia (NH3) as an easily removable additive together with low-boiling point, benign organic-water co-solvent mixtures as suspension media. We find that the addition of small amounts of NH3 as an additive drastically improves the obtainable LPE graphene concentrations by up to 2 orders of magnitude for a wide range of organic-water co-solvent mixtures including with isopropanol, methanol, ethanol, 1-propanol, tetrahydrofuran, acetonitrile, acetone, ethylene glycol and tert-butanol. With our approach we readily reach current benchmark graphene concentration values of ~180 mg·L-1 that are normally only obtainable using hard-to-remove high-boiling-point and hazardous standard solvents like dimethylformamide and 1-methyl-2-pyrrolydone or with hard-to-remove surfactants. Notably, NH3 as an additive is highly volatile and thus, as we show, easily removable without degrading the produced high quality graphene nanosheets.